Pengaruh Audit Operasional dan Pengendalian Internal terhadap Kinerja Karyawan pada Perumda BPR Garut - Sarah Felia Dwiayuni (Publikasi Indonesia, 2025)
Employee performance in the operational credit distribution process has not been effective and efficient, as indicated by employees' noncompliance with credit distribution procedures. This highlights the importance of internal control and operational audits in addressing the impact of employee behavior on performance, target achievement, and business efficiency. This study aims to examine the influence of operational audits and internal control on employee performance at Perumda BPR Garut. The research employs an explanatory method, using primary data collected through a closed-ended questionnaire. Hypothesis testing is conducted using a multiple linear regression model with the assistance of the Statistical Product and Service Solution (SPSS) version 25. The findings confirm that operational audits influence employee performance at Perumda BPR Garut, internal control affects employee performance, and both operational audits and internal control collectively impact employee performance. The study also reveals that operational audits and internal control at Perumda BPR Garut are not yet optimal, as some employees hold positions that do not align with their educational background, necessitating workshops and training to enhance competencies. Improving the quality of audit work programs by prioritizing high-risk areas and enhancing accuracy in audit documentation is essential to increase follow-up effectiveness. Furthermore, internal control remains suboptimal in areas such as training systems, task segregation, and managerial knowledge of fraud prevention. Therefore, evaluating training programs, implementing clearer task segregation, and enhancing interdepartmental communication are crucial to supporting more effective strategic decision-making.